IDENTIFIKASI SENYAWA FLAVONOID PADA FRAKSI ETIL ASETAT BENALU BATU (Begonia sp.) ASAL KABUPATEN MOROWALI UTARA - Agus Ritna; Syariful Anam; Akhmad Khumaidi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Benalu Batu Plant (Begonia sp.) in family Begoniaceae is a plant used by the people of North Morowali to treat tumors and cancers. It generally contains saponins, tannins, flavonoids and polyphenols. This research aimed to identify flavonoid compounds contained in ethyl acetate fraction of Begonia sp. The simplicia was extracted using maceration method and partitioned using n-hexane, ethyl acetate and water. The Ethyl acetate extract was then fractionated by nine eluent combinations using separation method of Vacuum Liquid Chromatography (VLC) and Preparative Thin Layer Chromatography (Prep TLC). One fraction was obtained and was suspected to contain flavonoid compounds after Shinode and Pew color reagent test. In the result of Ultraviolet-Visible Spectroscopy with methanol at wavelength range of 200-550 nm, the isolates showed absorption peaks at 275 nm (peak 1) and 225 nm (peak 2). Based on the wavelength of flavonoid compounds contained in the fraction, Begonia sp. showed similarities to the absorption peak of flavan-3-ol or flavanols